Surface morphology changes of lignin filled natural rubber latex films investigated using AFM in relation to tensile strengths - Asrul, M. (American Institute of Physics Inc., 2015)
The paper describes the preparation of lignin filled natural rubber latex composite and the consequential changes in tensile strength observed with varying lignin loading. The changes in tensile strength were shown to be associated with the changes in surface morphology as investigated via AFM. From the AFM analysis it can be inferred that lignin filled rubber latex film which exhibited an increase in tensile strength also demonstrated better phase homogeneity with lowest surface roughness value in comparison to the rest of the lignin filled rubber latex films analysed. Â© 2015 AIP Publishing LLC.